Own Data? Ethical Reflections on Data Ownership - Hummel, Patrik; Braun, Matthias; Dabrock, Peter (Philosophy & technology, 2021)
In discourses on digitization and the data economy, it is often claimed that data subjects shall be owners of their data. In this paper, we provide a problem diagnosis for such calls for data ownership : a large variety of demands are discussed under this heading. It thus becomes challenging to specify what—if anything—unites them. We identify four conceptual dimensions of calls for data ownership and argue that these help to systematize and to compare different positions. In view of this pluralism of data ownership claims, we introduce, spell out and defend a constructive interpretative proposal: claims for data ownership are charitably understood as attempts to call for the redistribution of material resources and the socio-cultural recognition of data subjects. We argue that as one consequence of this reading, it misses the point to reject claims for data ownership on the grounds that property in data does not exist. Instead, data ownership brings to attention a claim to renegotiate such aspects of the status quo .